1993
DOI: 10.1111/j.1600-0722.1993.tb01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Computerized planimetric method for clinical plaque measurement

Abstract: Soder P-0, Jin LJ, Soder B: Computerized planimetrie method for clinical plaque measurement. Scand J Dent Res 1993; 101: 21-5. © Munksgaard 1993 A computerized planimetric method for plaque area measurement has been developed. Using a computerized image analysis system (CIAS), the plaque area and tooth area on color slides were digitized and the number of pixels automatically counted. The proposed Plaque Percent Index (P' M. Index) expresses plaque area as a percentage of tooth area. The reproducibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 28 publications
(31 reference statements)
2
59
0
1
Order By: Relevance
“…Most clinical plaque indices measure a variable on an ordinal scale (ranked in an order and counted, ie 1,2,3, rather than measured), whereas an interval scale (measured as a difference between two units) is more powerful, providing more precise results and reducing clinical trial sizes 4 in addition to reducing subjectivity, increasing statistical strength and allowing better discrimination between similar products. Most clinical plaque indices yield ordinal data quickly, but are dependent upon a trained examiner's subjective evaluation 18 and a clinician to conduct examinations, increasing clinical trial costs.…”
Section: British Dental Journalmentioning
confidence: 99%
See 2 more Smart Citations
“…Most clinical plaque indices measure a variable on an ordinal scale (ranked in an order and counted, ie 1,2,3, rather than measured), whereas an interval scale (measured as a difference between two units) is more powerful, providing more precise results and reducing clinical trial sizes 4 in addition to reducing subjectivity, increasing statistical strength and allowing better discrimination between similar products. Most clinical plaque indices yield ordinal data quickly, but are dependent upon a trained examiner's subjective evaluation 18 and a clinician to conduct examinations, increasing clinical trial costs.…”
Section: British Dental Journalmentioning
confidence: 99%
“…4,21 Numerous studies have found computerbased plaque assessment more reliable 2,4,6,22 and more objective than classic plaque indices. 22 This technique offers linear measurements, increased reproducibility, 4 increased objectivity 2 and increased discriminating power. 23 The technique also has good correlation with plaque weight, viable microbial counts and visual assessment.…”
Section: British Dental Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…The area of plaque was given as a percentage of the total buccal surface just like it was done in the present study. We used a computer program to calculate the percentage of the plaque covered teeth surfaces from digital photographs similar to Söder et al and Eaton et al [26,27] . Further, Renton-Harper et al stated advantage of recording digital photographs as they are permanent records that can be re-evaluated at any point of time, and can later be transferred into other index scores; which helps in an easier comparison with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The ability to measure, although indirectly, plaque area within an objective planimetric system would be of advantage to researchers investigating plaque reduction following interventions. 22 The QLF technique may offer such measurement opportunities.…”
Section: Use Of Qlf As a Planimetric Devicementioning
confidence: 99%